Diagnostic performance of Thyroid Arterial Peak Systolic Velocity and Thyroxine Level as a Surrogate of Radioactive Iodine Uptake (Bangladesh Journal of Nuclear Medicine, 2025)
Introduction: Although the radioactive iodine uptake (RAIU) is regularly used for the assessment of thyrotoxicosis, its relationship with thyroxine (T4) level and the thyroid arterial peak-systolic velocity (PSV) deserves to be explored. Patients and methods: A retrospective study was done on a dataset comprising data from clinical work-up in a small series of patients with various entities of thyrotoxicosis. The RAIU, T4 level, and PSV from the inferior thyroid artery (ITA) were evaluated against RAIU. Moreover, the PSV index, calculated by dividing the PSV of ITA with the AP diameter of the corresponding thyroid lobe, and the T4 index, calculated by dividing the T4 level by the combined length of the anteroposterior (AP) diameters of the right and left lobes of the thyroid gland, were evaluated against RAIU. Receiver-operator characteristic (ROC) analysis was done to find out cut-off values for all those parameters that can be a surrogate for the RAIU categories at two and 24 hours. Result: The PSV of ≥ 42.6 cm/sec in the right ITA and a PSV of ≥ 36.8 cm/sec in the left ITA and a PSV index of 26 sec-1 in the left ITA were found as surrogates of RAIU ≥ 10% at two hours. The T4 index of ≥ 12.1 ng/dl/cm was found to be a surrogate of RAIU ≥ 25% at 24 hours. A PSV index of < 8.6 sec⁻¹ in the right ITA and < 8.9 sec⁻¹ in the left ITA were found as surrogates of RAIU < 4% at two hours. Conclusion: The cutoff values for the primary and derived parameters were determined in comparison with RAIU as the gold standard. Application of those values is expected to be clinically meaningful for the management of thyrotoxicosis.Bangladesh J. Nuclear Med. 27(2): 191-196, 2024